Laser‐induced Graphene‐based Non‐enzymatic Sensor for Detection of Hydrogen Peroxide. Issue 7 (5th April 2019) - Zhang, Yuhan; Zhu, Huichao; Sun, Pin; Sun, Chang‐Kai; Huang, Hui; Guan, Shui; Liu, Hailong; Zhang, Hangyu; Zhang, Chi; Qin, Kai‐Rong
Abstract: In this study, a laser‐induced graphene (LIG) loaded platinum nanoparticles (PtNPs) was prepared for precise, rapid and non‐enzymatic electrochemical detection of hydrogen peroxide (H2 O2 ). The commercial PI films were used as the substrate of LIG. In order to improve the electrochemical performance of LIG, a layer of PtNPs catalyst was fabricated through a magnetron sputtering process on the surface of LIG (PtLIG). Under optimized conditions, a linear relationship between H2 O2 reduction current and H2 O2 concentration was recorded, the correlation coefficient R 2 is 0.9919 with the detection limit of 0.1 μM (S/N=3) and the sensitivity of 248.4 μA mM −1 cm −2 . Moreover, the PtLIG exhibits excellent selectivity, reproducibility and repeatability. Because of these remarkable advantages, we believe that PtLIG will provide a wider range of applications in biosensors and bioelectronic devices. Abstract :